Why creating a general category of vulnerable countries is not suitable - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
As part of the preparation for the June Summit on financing, the question was raised as to whether a category of "vulnerable countries" should not be created or recommended. One would first have to ask who would be responsible for creating this category, so that it would be authoritative. Only the United Nations has the legitimacy to do so and a negative answer was given there when the question was asked five years ago. It could indeed be imagined that this position might change. But to understand what is at stake and examine the question in depth, it is necessary to recall this historical point.
Keywords: 330; Least developed Countries (LDCs); Vulnerabilities